Average BER evaluation of the uplink OFDM-based NOMA system under SIC and channel estimation error - Olawole, Akinbode A.; Balogun, Muyiwa B.; Offiong, Funmilayo B.; Obayiuwana, Enoruwa; Fisusi, Abimbola (Frontiers in Communications and Networks, 2024)
Non-orthogonal multiple access (NOMA) scheme has been recognized as a promising candidate for future generation wireless communication networks that requires high data rate and spectral efficiency. In order to achieve a superior spectral efficiency, the orthogonal frequency division multiplexing (OFDM) technique with robust channel estimation algorithm can be combined with the NOMA scheme. However, due to the inherent problem of inter-carrier interference in the OFDM-based systems, channel estimation using training symbols are not usually perfect.Furthermore, the successive interference cancellation (SIC) process commonly carried out in NOMA systems to address the interference among users is also imperfect under practical scenarios. Thus, a theoretical framework of the OFDM-based NOMA system to analyze the effect of both the imperfect SIC and channel estimation errors is presented in this paper. In particular, the effect of both the channel estimation errors and imperfect SIC, introduced at the receiver, on the bit error rate (BER) performance metric is analyzed under Rayleigh fading channel conditions.Our analytical results are compared to the corresponding simulation results for different design parameters. It is shown that the analytical and simulation results are in good agreement.